An influence of gamma-irradiation and ²³⁸U fragments on single-crystal silicon properties - Dovbnya, A.N.; Yefimov, V.P.; Pugachev, G.D.; Dyomin, V.S.; Dovbnya, N.A.; Gordienko, J.E.; Borodin, B.G.; Babychenko, S.V.; Semenets, T.A. (Вопросы атомной науки и техники, 2006)
In the paper the processes of accumulation of radiation defects, formed by fragments of ²³⁸U nucleus fission, for forming of amorphous phases in the bulk of single-crystal silicon and the influence of the temperature annealing of defects on the properties of disordered structures are investigated. Исследуются процессы накопления радиационных дефектов, образованных осколками деления ядер ²³⁸U, для формирования аморфных фаз в объеме монокристаллического кремния и влияния температуры отжига дефектов на свойства разупорядоченных структур. Досліджуються процеси накопичення радіаційних дефектів, утворених осколками ділення ядер ²³⁸U, для формування аморфних фаз в об'ємі монокристалічного кремнію та впливу температури віджига дефектів на властивості розупорядкованих структур.